THE INFORMATION ABOUT THE JAMA MASJID KALAI-AZIZON IN THE NEIGHBOURHOOD OF KALAI AZIZON IN KYZYLTEPO DISTRICT - Umedov Alisher Nematovich (Bright Mind Publishing, 2025)
Social and normative relations in all spheres of life of the residents of the Bukhara Emirate were strongly influenced by Islam and Sharia, which is its basis. The traditions, values, rituals, and holidays that have been preserved from centuries to centuries, have further strengthened loyalty to the traditions that have been preserved as an integral part of the people's lifestyle. In particular, the mass performance of religious ceremonies is considered to be a common characteristic of Islamic holidays with other traditions. In the Emirate of Bukhara, which is one of the major centers of Islam, there are centers of enlightenment, such as Bukhara and Samarkand, where there are places of education and the number of students was also quite large. A foreigner in Central Asia according to tourists and ambassadors, in the medieval Uzbek khanates Muslim education system is very well established, especially in Bukhara the emirate is considered one of the centers of Islamic enlightenment and the implementation of radical reforms National Revival, Spiritual Update, the National Idea, History in addressing functions of members of united society with strength The role of the science is growing. Inspection of the laws of historical development of Uzbekistan, for centuries, statehood, economic.